A preliminary study on calcium oxide as potential catalyst for gasification of palm oil empty fruit bunch to produce syngas - Khomah, Ismail; Yarmo, M.A.; Y. H, Taufiq-Yap; Aishah, Ahmad (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.